Macroeconomics and monetary policy : issues for a reforming economy - Ahluwalia, Montek S.; Reddy, Y. V.; Tarapore, S. S. (New Delhi ; New York : Oxford University Press, 2002)
Contributed articles with reference to India.
/ V. Sundararajan, Udaibir S. Das -- Monetary policy, internal debt, and anatomy of the Central Bank / S.S. Tarapore -- Dimensions of financial development, market reforms, and integration: the Indian experience / Y.V. Reddy -- The role of the debt market in infrastructure finanicing in India / A. Prasad, Rakesh Mohan.
Includes bibliographical references and index.
Keywords: Monetary policy -- India; Banks and banking -- India; International finance; India -- Economic policy -- 1991-